The TELL automatic sample changer for macromolecular crystallography. (31st March 2020) - Martiel, Isabelle; Buntschu, Dominik; Meier, Nathalie; Gobbo, Alexandre; Panepucci, Ezequiel; Schneider, Roman; Heimgartner, Peter; Müller, David; Bühlmann, Kevin; Birri, Mario; Kaminski, Jakub W.; Leuenberger, James; et al.
Abstract : The TELL sample changer has been developed at the Paul Scherrer Institute with a focus on speed, storage capacity and reliability, to serve the three macromolecular crystallography beamlines of the Swiss Light Source, as well as the SwissMX instrument at SwissFEL. Abstract : In this paper, the design and functionalities of the high‐throughput TELL sample exchange system for macromolecular crystallography is presented. TELL was developed at the Paul Scherrer Institute with a focus on speed, storage capacity and reliability to serve the three macromolecular crystallography beamlines of the Swiss Light Source, as well as the SwissMX instrument at SwissFEL.